Post-translational processing : a practical approach - Higgins, S. J. (Steve J.); Hames, B. D. (Practical approach series ;, 1999)
Post - Translational Modification: A Practical Approach and its companion volume Protein Expression: A Practical Approach form the final part of the PAS mini-series on protein synthesis and processing. This volume begins with a chapter on protein sequencing followed by a chapter on protein folding and import into organelles. The next three chapters cover the three major forms of covalent modification: phosphorylation, glycosylation, and lipid modification. Proteolytic processing the is the next topic and the final two chapters are concerned with protein turnover in mammalian cells and yeast. This book is a comprehensive volume of the best current methodology and is designed to be used at the bench or away from the bench to gain insight into future experimental approached.